Efforts of Migrant Care and the Indonesian Government in Realizing the Protection of Indonesian Migrant Workers (PMI) Facing the Death Penalty in Saudi Arabia (2015 – 2018) - Prebia Prakarsa Renta; Arie Kusuma Paksi (Sociología y Tecnociencia, 2023)
One of Indonesia’s numerous issues is the size of its workforce. The Indonesian government’s solution is to send Indonesian female migrant workers in the informal sector overseas, including to Saudi Arabia. These difficulties can be divided into three categories: light, moderate, and severe—the death penalty. The death penalty represents the most extreme level of the issue. From 2015 to 2018, several Indonesian female migrant workers in Saudi Arabia’s informal sector had been sentenced to death without any notification from the Saudi Arabian government to the Indonesian government, including the execution of Siti Zaenab in 2015 and the Tuti Tursilawati in 2018 It prompted Migrant Care and the Indonesian government to assist in the execution of Indonesian migrant workers (PMI) in the informal sector.